Current Trends In The Foreign Languages Learning-Acquisition: The French Foreign Language Didactics - Silvia Rodríguez Díez (FahrenHouse, 2010)
Analysis of the didactics in foreign languages learning accross concepts and methods. Description of the different trends evolution taken for a second language learning or acquisition: discussions and critics. The new perspective of learning in this area: the communi- cative approach. A specific treatment is given for the French Foreign Language case.